2022
DOI: 10.3390/nu14122431
|View full text |Cite
|
Sign up to set email alerts
|

A Produce Prescription Program in Eastern North Carolina Results in Increased Voucher Redemption Rates and Increased Fruit and Vegetable Intake among Participants

Abstract: Few produce prescription programs have taken place in rural areas, in the context of existing public health programs. Thus, the purpose of this mixed-methods study was to examine voucher redemption rates, change in fruit and vegetable intake, and suggestions for improvement among participants enrolled in a produce prescription program occurring in existing public health programs throughout rural eastern North Carolina. We examined voucher redemption rates and conducted pre- (n = 125) and post-intervention surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Transportation was not perceived as a consistent or major issue in this study, suggesting that partnering with grocery outlets may make using the incentive more convenient and feasible. Future programs could consider partnering with multiple grocery retailers to increase produce offerings so that participants would be able to choose where to redeem the incentive, which was important to many participants in our study and in others ( 35 , 44 , 46 ). Moreover, this program only covered fresh produce yet expanding eligible items to include minimally processed (e.g., no added sugar) frozen produce, that are as nutritious for meeting the needs of healthy diet, may increase the storability, use of purchase items, less frequent trips to stores ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transportation was not perceived as a consistent or major issue in this study, suggesting that partnering with grocery outlets may make using the incentive more convenient and feasible. Future programs could consider partnering with multiple grocery retailers to increase produce offerings so that participants would be able to choose where to redeem the incentive, which was important to many participants in our study and in others ( 35 , 44 , 46 ). Moreover, this program only covered fresh produce yet expanding eligible items to include minimally processed (e.g., no added sugar) frozen produce, that are as nutritious for meeting the needs of healthy diet, may increase the storability, use of purchase items, less frequent trips to stores ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with an evaluation of a produce prescription program in which participants reported that they had faced challenges with accessing high-quality fruits and vegetables before the COVID-19 pandemic and these challenges worsened during the pandemic ( 39 ). A study conducted by Lyonnais and colleagues found that participants reported that available locations where vouchers could be redeemed did not have the foods they were looking for and that this was a barrier to voucher redemption ( 29 ). Esquivel and colleagues documented similar concerns among participants in a pediatric produce prescription program ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Client experiences of programs is a process indicator of person-centeredness, while client satisfaction is an outcome of client experiences of programs that reflects the extent to which the services provided meet their needs and expectations (22). Although a growing body of literature has explored client experiences and satisfaction with produce prescription programs (23)(24)(25)(26)(27)(28)(29)(30), there is still a need to better understand whether program clients feel they are treated with respect and dignity, a key domain of positive client experiences (22,31). Furthermore, more input and insights from clients on how produce prescription programs can promote positive experiences can be useful for informing the design and delivery of person-centered and respectful programs.…”
Section: Introductionmentioning
confidence: 99%